Agronegócio canavieiro em Alagoas : controle do território e luta por terra - Almeida, Ricardo Santos de (2016)
This research explains the production of rural areas of Alagoas State from the occupation and use of the land by the sugarcane farming industry. Agro-industrial economic activity is fed by the privileges afforded to the social group that controls politics, which exposes the political tentacles of this economic activity in the state. The relationship between the economic system of the sugar mills (here considered in their relationship with the political system) and the production restructuring process that has taken place, starting in the last twenty years of the 20th century, explains why the sugarcane farming activity in Alagoas is maintained and its relationship with the continuing poverty that can be seen on a daily basis in the landscape. This also explains the strategies for social reproduction employed by rural workers who have no access to land. The resistance of the social movements that are found in the territory in the municipalities of Junqueiro, Campo Alegre and Teotônio Vilela reaffirms the struggle in the countryside on land belonging to the mills or to sugarcane business groups. In this sense, the research shows the necessity to interpret the process and the historical heritage to reveal the repercussions that the restructuring of agricultural production have on the lives of the rural population. Subjection of the land to capital in this reality is a situation made possible by the political and economic actions that mark out the State of Alagoas. In this sense, production restructuring in the sugarcane farming activity results in a strengthening of the agribusiness, thus reaffirming the permanence of the oligarchical rural base that for centuries has exercised its power over the territory of Alagoas.